Peningkatan Motivasi Pembelajaran Membaca Tabel Dan Grafik Menggunakan Pendekatan Contexstual Teaching And Learning di Sekolah Menengah Atas - Budi Santuso (Jurnal Guru Indonesia, 2021)
AbstractThis study aims to determine and analyze the motivation and learning achievement of class XII IPS 2 SMA Negeri Jenggawah students in the odd semester Indonesian language subject for the 2019/2020 school year after participating in learning with problem-solving methods. In addition, to determine the level of effectiveness in achieving the target of learning completeness. The approach used is Stephen Kemmis' "Cyclical" model of action research. The research subjects were students of class XII IPS 2 SMA Negeri Jenggawah for the academic year 2019/2020 with a total of 40 students. Data were collected by means of achievement tests in the form of essays, motivational scales, observation guidelines, and interviews. Data analysis was carried out by analytical descriptive. The research findings show: (1) the use of the CTL method in learning Indonesian in class XII IPS 2 SMAN Jenggawah in the odd semester of the 2019/2020 school year can increase students' learning motivation. Based on the results of the analysis in cycle 1 and cycle 2, the use of the CTL learning method was quite effective in increasing students' motivation and learning achievement in learning Indonesian in class XII IPS 2 SMAN Jenggawah. The number of students whose learning motivation is high and very high reaches 90% and the number of students whose learning has been completed reaches 82.5%.Keywords:  the effectiveness, CTL method, reading, table, graphic AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis motivasi dan prestasi belajar siswa kelas XII IPS 2 SMA  Negeri Jenggawah pada mata pelajaran Bahasa Indonesia. mengikuti pembelajaran dengan metode pemecahan masalah. Di samping itu juga untuk mengetahui tingkat efektivitasnya dalam mencapai target ketuntasan pembelajaran. Pendekatan yang digunakan adalah riset aksi model “Cyclical” Stephen Kemmis. Subjek penelitian adalah siswa kelas XII IPS 2 SMA Negeri Jenggawah. Data dikumpulkan dengan tes prestasi berbentuk essay, skala motivasi, pedoman observasi, dan wawancara. Analisis data dilakukan secara deskriptif analitik. Temuan penelitian menunjukkan bahwa penggunaan metode CTL dalam pembelajaran Bahasa Indonesia di kelas XII IPS 2 SMAN Jenggawah ternyata dapat meningkatkan motivasi belajar siswa. Berdasarkan hasil analisis pada siklus 1 dan siklus 2, metode pembelajaran  CTL ternyata cukup efektif meningkatkan prestasi serta motivasi belajar siswa dalam pembelajaran Bahasa Indonesia di kelas XII IPS 2 SMAN Jenggawah. Jumlah siswa yang motivasi belajarnya tinggi dan sangat tinggi mencapai 90% dan jumlah siswa yang belajarnya telah tuntas mencapai 82.5%.Kata kunci:  efektifitas, metode CTL, membaca, tabel, grafik.